2002
DOI: 10.1016/s0960-9822(02)01338-6
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging of Telomeres

Abstract: Interphase positioning of telomeres can be achieved through two partially redundant mechanisms. One requires the heterodimeric yKu complex, but not Mlp1 and Mlp2. The second requires Silent information regulators, correlates with transcriptional repression, and is specific to S phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
154
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(167 citation statements)
references
References 49 publications
12
154
1
Order By: Relevance
“…This absence would very likely have implications for the local chromatin structure, and indeed we have shown that the histones of inactive and active var genes are differentially acetylated (12). Experiments in yeast (29,30), Drosophila (31), and mammalian systems (32) demonstrate that genes can be recruited from one area of the nucleus to another to be repressed. These recruitments are sometimes The same var gene is in a silenced state.…”
Section: Discussionmentioning
confidence: 88%
“…This absence would very likely have implications for the local chromatin structure, and indeed we have shown that the histones of inactive and active var genes are differentially acetylated (12). Experiments in yeast (29,30), Drosophila (31), and mammalian systems (32) demonstrate that genes can be recruited from one area of the nucleus to another to be repressed. These recruitments are sometimes The same var gene is in a silenced state.…”
Section: Discussionmentioning
confidence: 88%
“…There is precedent for chromatin proteins involved in transcription repression and present in limiting con- centrations being relocalized to sites of DNA damage in the cell, resulting in derepression of normally silent transcription units. For example, the Ku and SIR silencing proteins are normally sequestered at telomeres in Saccharomyces cerevisiae (54,73,74). However, after the introduction of DNA damage, these proteins are relocalized from the telomeres to DNA repair sites (75,76), resulting in derepression of genes normally silenced by telomere position effect (77).…”
Section: Up-regulation Of Silent Ess Correlates With a Block In Smentioning
confidence: 99%
“…Centromeres of each chromosome cluster near the spindle pole body (SPB), 2,3) and telomeres bind to the nuclear envelope. [4][5][6][7] These localizations switch between the G 1 and S phases. Centromeres and telomeres move to the replication factory in the central region of the nucleus in the S phase.…”
mentioning
confidence: 94%